The impact of detraining on performance and some of the biomechanical variables in taekwondo - Kilani, H. A.; Nasser, W. S. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Twenty players (aged 9 - 13 yrs) were divided into two equivalent groups ( 10 each ) based on ( age , height , weight , training age and the selected biomechanical variables).The 1st group ( fixed training) trained by the round house kick from ready position (stance) while the 2nd group ( variant training ) trained using different types of the skills' execution. Both group trained there times a week (75 Minutes) for 6 weeks and measurements were taken for the post test, one week later of detraining and two weeks later of detraining, for fixed training and variant training. No significant differences were observed between the two groups in the posttest and first detraining. It is recommended that both training regimen are important to conserve the level of achieved performance after 2 weeks of detraining.